Faktor-faktor yang Berkontribusi terhadap Kesuksesan Proyek Pengedokan Kapal - Muhammad Ikhwan Kurniawan; Ervina Ahyudanari (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
Vessel as a main mode of sea transportation that support logistics activities in Indonesia were required to drydocking regularly. Drydocking projects often experiences various challenges that make it difficult to meet the project success criteria. This study aims to examine the contribution of leadership, project management, communication, human resource, and environment factors on the successful drydocking project. A cross-sectional survey using purposive sampling method was conducted on 47 respondents consisting of project leaders, supervisors, staff and production executive of the project. Pearson correlation analysis show that leadership, project management and human resource partially have positive correlation in project success. Furthermore, using multiple regression analysis found that leadership, project management, communication, human resources and environment factor simultaneously have impact to project success with leadership factor is the most contributed. According this research, shipyards need to pay more attention in project leadership by assign qualified project manager